Experimentally manipulated sleep duration in adolescents with asthma: Feasibility and preliminary findings. Issue 12 (14th April 2015) - Meltzer, Lisa J.; Faino, Anna; Szefler, Stanley J.; Strand, Matthew; Gelfand, Erwin W.; Beebe, Dean W.
Summary: Objective: To examine the impact of sleep duration on lung function and asthma symptoms in adolescents. Methods: Ten adolescents with asthma (60% female, 60% Caucasian, mean age = 13.7 years, range 12–17) completed a 3‐week randomized, cross‐over sleep manipulation protocol. Following a week of self‐selected sleep duration, adolescents were randomized to a five‐night deficient sleep opportunity (6.5 hr in bed) or a healthy sleep opportunity (10 hr in bed) obtained by systematically changing bedtimes. Wake time remained consistent across all 3 weeks (including weekends). Daily reports of sleep patterns and asthma symptoms, actigraphy, and daily peak expiratory flow rates (PEFR), as well as weekly spirometry and exhaled nitric oxide were collected. Results: Participants averaged 3.2 hr less sleep ( P  < 0.001) per night in the short sleep condition versus the long sleep condition. Further, they had an 8.4% decrease overnight in PEFR ( P   =  0.007), and reported more asthma symptoms interfering with activities in the past 24 hr ( P  = 0.02) in the short sleep condition than the long sleep condition. No significant differences between experimental weeks were found for weekly spirometry or exhaled nitric oxide. Conclusions: This pilot study demonstrated the feasibility of a cross‐over sleep manipulation protocol in adolescents with asthma. Since overnight decrease in PEFR is a marker of nocturnal asthma, and has been associated with the severity of daytime airflow limitation, these early‐stage results suggest that shortened sleep duration may exacerbate adolescent asthma and associated functional impairments.Pediatr Pulmonol. 2015; 50:1360–1367. © 2015 Wiley Periodicals, Inc.